Design of Highly Potent, Dual‐Acting and Central‐Nervous‐System‐Penetrating HIV‐1 Protease Inhibitors with Excellent Potency against Multidrug‐Resistant HIV‐1 Variants. (15th March 2018) - Ghosh, Arun K.; Rao, Kalapala Venkateswara; Nyalapatla, Prasanth R.; Kovela, Satish; Brindisi, Margherita; Osswald, Heather L.; Sekhara Reddy, Bhavanam; Agniswamy, Johnson; Wang, Yuan‐Fang; Aoki, Manabu; Hattori, Shin‐ichiro; Weber, Irene T.; et al.
Abstract: Herein we report the design, synthesis, X‐ray structural, and biological studies of an exceptionally potent HIV‐1 protease inhibitor, compound5 ((3 S, 7a S, 8 S )‐hexahydro‐4 H ‐3, 5‐methanofuro[2, 3‐ b ]pyran‐8‐yl ((2 S, 3 R )‐4‐((2‐(cyclopropylamino)‐ N ‐isobutylbenzo[ d ]thiazole)‐6‐sulfonamido)‐1‐(3, 5‐difluorophenyl)‐3‐hydroxybutan‐2‐yl)carbamate). Using structure‐based design, we incorporated an unprecedented 6‐5‐5‐ring‐fused crown‐like tetrahydropyranofuran as the P2‐ligand, a cyclopropylaminobenzothiazole as the P2′‐ligand, and a 3, 5‐difluorophenylmethyl group as the P1‐ligand. The resulting inhibitor5 exhibited exceptional HIV‐1 protease inhibitory and antiviral potency at the picomolar level. Furthermore, it displayed antiviral IC50 values in the picomolar range against a wide panel of highly multidrug‐resistant HIV‐1 variants. The inhibitor shows an extremely high genetic barrier against the emergence of drug‐resistant variants. It also showed extremely potent inhibitory activity toward dimerization as well as favorable central nervous system penetration. We determined a high‐resolution X‐ray crystal structure of the complex between inhibitor5 and HIV‐1 protease, which provides molecular insight into the unprecedented activity profiles observed. Abstract : Crystal clear : We report the structure‐based design, synthesis, biological evaluation, and X‐ray structural studies of a series of exceptionally potent HIV‐1 protease inhibitors containing novel P1, P2, and P2′ ligands to interact with active site residues. Inhibitor5 shows exceptional HIV‐1 inhibitory and antiviral potency at the picomolar level. An X‐ray structure of the inhibitor5 ‐bound HIV‐1 protease complex provides molecular insight into the unprecedented activity profiles.